Inside and outside the multiplex. Business studies on cinema audiences in Latin America - Valencia, Juan Carlos (2016)
Current systems to research cinema audiences inside contemporary cultural industries are little known beyond insider circles. Nevertheless, the quantitative data used by producers, distributors and exhibitors have significant impacts on moviegoers, public policy agents and even on academic researchers. ¿How are cinema audiences quantified and researched in Latin America? Is the data reliable? The article concludes that commercial audience research in Latin America and the world basically measures tickets sold in theaters but does not study other forms of cinema consumption, not even the rich and complex appropriations and relations that people establish with films.